2012
DOI: 10.4028/www.scientific.net/amr.602-604.627
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and High Temperature Mechanical Properties of Inconel 713C by Using Metal Injection Molding

Abstract: Inconel 713C alloy was tried to manufacture by using MIM(Metal Injection Molding) process. The high-temperature mechanical properties of MIMed Inconel 713C were also investigated. Processing defects such as pores and binders could be observed near the surface. Tensile tests were conducted from room temperature to 900°C. The result of tensile tests showed that this alloy had similar or somewhat higher strengths (YS: 734 MPa, UTS: 968 MPa, elongation: 7.16 % at room temperature) from RT to 700°C than those of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As it is reported in literature, the sintering temperature of metal injection moulded nickel-based superalloys has to be close or even slightly above the solidus temperature of the respective alloy. [3][4][5][6][7][8] For this reason, dilatometry measurements were performed in a temperature range of 1270 to 1325°C to investigate the sintering behaviour of MIM brown parts and to find suitable sintering temperatures.…”
Section: Dsc Thermocalc and Dilatometrymentioning
confidence: 99%
See 2 more Smart Citations
“…As it is reported in literature, the sintering temperature of metal injection moulded nickel-based superalloys has to be close or even slightly above the solidus temperature of the respective alloy. [3][4][5][6][7][8] For this reason, dilatometry measurements were performed in a temperature range of 1270 to 1325°C to investigate the sintering behaviour of MIM brown parts and to find suitable sintering temperatures.…”
Section: Dsc Thermocalc and Dilatometrymentioning
confidence: 99%
“…Over the last decade MIM capability of several nickel-based superalloys like Inconel 625, Inconel 713, Inconel 718, Nimonic 90, Udimet 720 and MAR-M-247 has been investigated. [3][4][5][6][7][8] The studies so far showed promising results, i.e. good mechanical properties at high temperatures as well as good hightemperature oxidation behaviour have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a continuous demand for shifting the operating temperature to higher values, especially in the automotive and aircraft industry, combined with the need of cost-effective mass production of the respective parts [1]. K418 alloy is a precipitation hardening-type alloy of Ni-Cr-Al-Mo-Nb composition with excellent high temperature mechanical properties, castability, oxidation resistance and thermal fatigue resistance [2].…”
Section: Introductionmentioning
confidence: 99%